2023
DOI: 10.1097/inf.0000000000004009
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Group A Streptococcus Rapid Antigen Detection Test on Middle Ear Fluid in Children With Acute Otitis Media With Spontaneous Perforation: A Prospective Multicenter Evaluation

Abstract: Group A Streptococcus is one of the leading causes of otorrhea. The performance of rapid antigen tests in 256 children with otorrhea showed excellent sensitivity, 97.3% (95% confidence interval: 90.7%–99.7%), and specificity, 100% (95% confidence interval: 98.0%–100%). In a period of increasing invasive and noninvasive group A Streptococcus infections, an early diagnosis could be useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Although the design of the present study is not the same, rapid antigen tests that are developed with immunochromatographic methods for the rapid diagnosis of S. pyogenes are widely used for diagnostic purposes [ 36 , 37 , 38 ]. In their study, Reijtman et al attempted to develop an immunochromatographic method to detect S. pyogenes antigen directly from clinical samples and positive blood culture bottles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the design of the present study is not the same, rapid antigen tests that are developed with immunochromatographic methods for the rapid diagnosis of S. pyogenes are widely used for diagnostic purposes [ 36 , 37 , 38 ]. In their study, Reijtman et al attempted to develop an immunochromatographic method to detect S. pyogenes antigen directly from clinical samples and positive blood culture bottles.…”
Section: Discussionmentioning
confidence: 99%
“…GAS is known to be among the most common bacterial pathogens, especially in children who are older than 3 years, and the incidence of GAS infections has increased in invasive and non-invasive forms in recent years. GAS also frequently causes middle ear infections in children between the ages of 3 months and 15 years [ 37 ]. Cohen et al conducted a multicenter immunochromatographic test trial in children who had middle ear infections and found that the performance of this test had a very high sensitivity [97.3%] and specificity [100%] when compared to the culture method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation